A new giant species of Acrophylla Gray, 1835 (Phasmida: Phasmatidae: Phasmatini) from the highlands of the Wet Tropics, Queensland, Australia. - Coupland, Ross M.; Emmott, Angus J. (Zootaxa, 2025)
Searching of suitable habitat during the wet season months has revealed a spectacular new species of phasmid from Queensland, Australia: Acrophylla alta sp. nov., which is described and figured from the holotype and paratype females only, also eggs. A key is provided to compare it with other similar species within the genus. Habitat type and known foodplants are noted.